2010
DOI: 10.1007/s10534-010-9298-0
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract

Abstract: In this study, Lactobacillus casei was used to deliver and express human lactoferrin (hLF) to protect the host against bacterial infection. Full-length hLF cDNA was cloned into a Lactobacillus-specific plasmid to produce the L. casei transformants (rhLF/L. casei). Antimicrobial activity of recombinant hLF was examined in inhibition of bacteria growth in vitro. A mouse model was established to test in vivo antibacterial activity and protective effect of orally-administered probiotic L. casei transformant in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 48 publications
0
33
0
1
Order By: Relevance
“…Our recent studies also revealed that probiotic Lactobacillus casei expressing human LF exhibit antibacterial activity on E. coli ATCC 25922 both in vitro and in vivo (Chen et al 2010). In another previous study, we demonstrated increased villous length in the small intestines of mouse pups fed pLFenriched milk from transgenic females, compared with the length of villi in mice fed wild-type milk (Wu et al 2007).…”
Section: Animal Studiesmentioning
confidence: 87%
“…Our recent studies also revealed that probiotic Lactobacillus casei expressing human LF exhibit antibacterial activity on E. coli ATCC 25922 both in vitro and in vivo (Chen et al 2010). In another previous study, we demonstrated increased villous length in the small intestines of mouse pups fed pLFenriched milk from transgenic females, compared with the length of villi in mice fed wild-type milk (Wu et al 2007).…”
Section: Animal Studiesmentioning
confidence: 87%
“…casei engineered to express human lactoferrin exhibited antimicrobial activity in the gastrointestinal tract against enteric pathogens both in vitro and in vivo. 81 This recombinant strain also protected from pathogen-induced tissue injury. Bioengineered probiotics were also able to control pathogen transmission by insects.…”
Section: Antimicrobial Action Of Bioengineered Probioticsmentioning
confidence: 92%
“…Lung tissue was fixed in 10% buffered formaldehyde (pH 7.0), embedded with paraffin, sectioned into 3  μ m sections, and examined using hematoxylin and eosin (H&E) staining as described previously [29, 30]. …”
Section: Methodsmentioning
confidence: 99%